MAKE WEBSITE AGENTS PRINT MEDIA M-JENSOS & ADVERTISING AGENCY USING MACROMEDIA DREAMWEAVER MX - Mardiansyah Mardiansyah; Linda Wahyu Widianti, SKom, MMSI (Jurnal Sistem Informasi, 2007)
Today technology is growing rapidly, where human needs information superhighway.Especially with the internet facility which began ogled as a media campaign that wasquite interesting.For that the author wants to give agents information about the print media MJENSOSAGENCY&ADVERTISING to customers who want to subscribe to theprint media and advertising. The site is expected to provide convenience for peoplewho want to subscribe the print media and advertising.